HPV Positive Status Is a Favorable Prognostic Factor in Non-Nasopharyngeal Head and Neck Squamous Cell Carcinoma Patients: A Retrospective Study From the Surveillance, Epidemiology, and End Results Database - Wu, Qiuji; Wang, Miao; Liu, Yixin; Wang, Xulong; Li, Yi; Hu, Xiaoyan; Qiu, Ye; Liang, Wenjing; Wei, Yongchang; Zhong, Yahua (Frontiers in Oncology, 2021)
Objective To investigate the impact of the human papillomavirus (HPV) status on head and neck squamous cell carcinoma (HNSCC) arising from different anatomic subsites. Methods HNSCC patients with known HPV status from the Surveillance, Epidemiology, and End Results (SEER) database between 2010–2015 were included in our analysis. Patients were classified into three categories of HNSCC according to Site recode ICD-O-3/WHO 2008 and Primary Site-labeled, namely, oropharynx, hypopharynx, and nasopharynx. Logistic regression model was conducted to evaluate the relationship between patient characteristics and HPV status. Kaplan-Meier methods and COX regression analysis were used to analyze survival data. Results A total of 9,943 HNSCC patients with known HPV status from the SEER database were enrolled, with 6,829 (68.7%) HPV-positive patients. HPV-positive and HPV-negative HNSCC were distinct and had different clinical and socioeconomic features (all P < 0.001). Primary sites, socioeconomical factors (age, sex, marital status, and race), and pathological features (TNM stage and grade) were closely related with HPV status (all P < 0.001). HPV-positive status was a favorable prognostic marker in HNSCC patients with cancers of the oropharynx and hypopharynx (all P < 0.001), but was not in nasopharyngeal carcinoma patients (P = 0.843). A total of 8,933 oropharyngeal carcinoma (OPC) and 558 hypopharyngeal carcinoma (HPC) patients were divided into the training and validation cohorts with a ratio of 1:1. Significant prognostic factors of the OS yielded by multivariate COX analysis in the training cohort were integrated to construct nomograms for OPC and HPC patients. The prognostic models showed a good discrimination with a C-index of 0.79 ± 0.007 and 0.73 ± 0.023 in OPC and HPC, respectively. Favorable calibration was reflected by the calibration curves. Additionally, corresponding risk classification systems for OPC and HPC patients based on the nomograms were built and could perfectly classify patients into low-risk, intermediated-risk, high-risk groups. OS in the three risk groups was accurately differentiated and showed a good discrimination. Conclusion HPV positivity was associated with an improved survival in HNSCC patients with cancers of the oropharynx and hypopharynx. Nomograms and corresponding risk classification systems were constructed to assist clinicians in evaluating the survival of OPC and HPC patients.